EROSI DAN SEDIMENTASI DI DAERAH ALIRAN SUNGAI (DAS) CITARUM HULU DAN UMUR OPERASIONAL PLTA SAGULING - -, Edi Tri Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2013)
Upper Citarum Catchments Area which is a function as buffer of Saguling Dam, has been pressuring to bear heavy loads. Various studies have been done, but still required analysis, discussion and identification of sources of erosion, and sedimentation that affect the operational life time of Saguling Hydroelectric Power Dam . The rate of erosion and sedimentation analysis done based on secondary data research / previous measurement. Satellite imagery